(untitled) - Ngô, Vĩnh Long (New York, 1991)
This book is likely to serve as a forceful, unpleasantly chilling introduction to some very representative Vietnamese views about what Vietnamese relations with the industrial West, the social result, in rural areas, of the policies of French colonial administrators in Vietnam between the 1880s and 1945
Keywords: Vietnam,Việt Nam; Rural conditions,Điều kiện nông thôn